Volunteerism, organizational justice and organizational commitment: the case of sport coaches in Malaysian schools - Ooi, Cheng Lee; Yusof, Aminuddin; Soh, Kim Geok; Omar, Zoharah (Human Resource Management Academic Research Society, 2017)
The purpose of this study was to examine the perceptions of volunteer coaches in Malaysian schools about the relationship between organisational justice and organisational commitment. A cross-sectional correlational study using mail survey was conducted on 750 Malaysian school volunteer coaches. The subjects were selected using proportionate stratified and simple random sampling techniques. The data were analysed using structural equation modeling with AMOS. Path analysis showed that only interpersonal justice was related to affective commitment. Interpersonal justice creates a sense of belongingness and internalisation with the organisation value and norm, thus fostering higher affective commitment by willing to stay and strive for organisational goals. The results also show interpersonal justice to be negatively related with continuance commitment. This suggests that by providing fairer interpersonal treatment (i.e. interpersonal justice), the authorities would lower the volunteer coaches’ psychological engagements in continuance commitment. Distributive justice was found to be significantly related to normative commitment. Based on social exchange theory (Blau, 1964) if volunteer coaches are given opportunity through providing fair resources allocation and sports equipment, they would harness their effort to fully engage in coaching, in exchange, they would increase their normative commitment.